Ethnic differences in the effect of environmental stressors on blood pressure and hypertension in the Netherlands - Lindeman Ellen; Ujcic-Voortman Joanne K; Wendel-Vos Wanda; van Hooijdonk Carolien; Agyemang Charles; Stronks Karien; Droomers Mariel (BMC, 2007)
Abstract Background Evidence strongly suggests that the neighbourhood in which people live influences their health. Despite this, investigations of ethnic differences in cardiovascular risk factors have focused mainly on individual-level characteristics. The main purpose of this study was to investigate associations between neighbourhood-level environmental stressors (crime, housing density, nuisance from alcohol and drug misuse, quality of green space and social participation), and blood pressure (BP) and hypertension among different ethnic groups. Methods Individual data from the Amsterdam Health Survey 2004 were linked to data on neighbourhood stressors creating a multilevel design for data analysis. The study sample consisted of 517 Dutch, 404 Turkish and 365 Moroccans living in 15 neighbourhoods in Amsterdam, the Netherlands. Results Amongst Moroccans, high density housing and nuisance from drug misuse were associated with a higher systolic BP, while high quality of green space and social participation were associated with a lower systolic BP. High level of nuisance from drug misuse was associated with a higher diastolic BP. High quality of green space was associated with lower odds of hypertension. Amongst Turkish, high level of crime and nuisance from motor traffic were associated with a higher diastolic BP. Similar associations were observed among the Dutch group but none of the differences were statistically significant. Conclusion The study findings show that neighbourhood-level stressors are associated with BP in ethnic minority groups but were less evident in the Dutch group. These findings might imply that the higher BP levels found in some ethnic minority groups might be partly due to their greater susceptibility to the adverse neighbourhood environment in which many ethnic minority people live. Primary prevention measures targeting these neighbourhood stressors may have an impact in reducing high BP related morbidity and mortality among ethnic minority groups.